The Role of Monetary Policy using the Taylor´s Rule under High Level Indebtedness: The Brazilian Case - MELO, MARCELO; GOMES, WELIGTON (Archives of Business Research, 2020)
This research investigated if the Central Bank of Brazil follows the Taylor´s rule under high indebtedness. Research data collected covered last 25 years from Dec/1995 until Feb/2020 from the Central Bank of Brazil and methodology applied was vector auto-regression (VECM) analysis with five macroeconomic variables as follows: Government net Debt to GDP (DEBT/GDP), Gross Domestic Product (GDP), Exchange Rate (EXRATE), Consumer Price Index (IPCA) and Interest Rate (SELIC). Government´s indebtedness in relation to Brazilian GDP doubled from January/2014 up to Mar/2020, what make this research an outstanding issue. Conclusively the high-level debt environment interferes in the Central Bank of Brazil policy. Therefore, the Taylor´s rule is not being followed as it is expected for inflation rate targeting control. With respect economic activity monitoring the Central Bank of Brazil still applies the Taylor´s rule, increasing the interest rate in overheated economic activity periods.